Let's complete the square step by step for the equation \( x^2 + 12x - 14 = 0 \).
-
Starting with the original equation: \[ x^2 + 12x - 14 = 0 \]
-
Move the constant term to the other side: \[ x^2 + 12x = 14 \]
-
Identify the coefficient of \( x \), divide by 2, and square it:
- Coefficient of \( x \) is 12.
- Half of 12 is 6, and \( 6^2 = 36 \).
-
Add the squared term to both sides: \[ x^2 + 12x + 36 = 14 + 36 \]
-
Simplify the right side: \[ x^2 + 12x + 36 = 50 \]
-
Factor the left side: \[ (x + 6)^2 = 50 \]
-
Take the square root of both sides:
- Remember to consider both the positive and negative roots. \[ x + 6 = \pm \sqrt{50} \]
-
Isolate the variable \( x \): \[ x = -6 \pm \sqrt{50} \]
-
Final answers:
- Since \( \sqrt{50} = 5\sqrt{2} \), we can rewrite the answers as: \[ x = -6 + 5\sqrt{2} \quad \text{or} \quad x = -6 - 5\sqrt{2} \]
So, filled in response areas would be:
- Response area 1: \( 36 \)
- Response area 2: \( 36 \)
- Response area 3: \( \pm \sqrt{50} \)
- Response area 4: \( -6 \pm \sqrt{50} \)
- Response area 5: \( -6 \pm 5\sqrt{2} \)